A Long-term View on the Business Model of Newspaper Publishing: International Comparison and Quantitative Modelling for Germany as Case in point. (22nd September 2016) - Kolo, Castulus
Although consequences are still debated, financials in several countries indicate that the traditional newspaper publishers' business is not sustainable in the long term. To overcome speculation we built a quantitative model for newspapers' profit margins to derive ten-year scenarios in a systematic way. The simulation is based on a conceptualisation of a 'business model' that can be operationalized. It was designed and tested for specific newspapers in Germany, but is based on general assumptions and of international applicability. Even with optimistic values for print-online substitution, online usage still on the rise, and mobile devices becoming widespread, additional digital revenues of newspapers' brands most likely cannot compensate for losses in print. In addition to exploiting editorial content across multiple platforms, publishers should explore options beyond these: developing 'dynamic capabilities' and possibly setting-up 'ambidextrous' organizations. (Unless, of course, they wait for subsidies to manifest or rely on an engagement of civil society for financing journalism.)